Clustering technique for analysing environmental attitude among undergraduate students in Purulia district, West Bengal - Subir Sen; Surajit Mahato; Ramesh Chandra Mahato; Bishal Das (Journal of Social Studies, 2025)
This study aims to explore inter-dimension relationships in the environment, identifying clusters based on independent variables (Stream, gender, location) and their consequences on Environmental Behaviour (EB), Environmental Opinion (EO), and Environmental Emotion (EE) among undergraduates in Purulia district, West Bengal. Using a descriptive survey method with randomly sampled participants, the study employs the "Environmental Attitude Scale" developed by Uzun et al. (2019) and statistical techniques such as the Product Moment Method for calculate and Two-Step Clustering techniques. The results reveal significant correlations between Environmental Behaviour (EB), Environmental Emotion (EE), Environmental Attitude (EA), and Environmental Opinion (EO). Factors like Stream, gender, and location contribute to distinct clusters, emphasizing their influence on environmental aspects. Overall, the study provides valuable insights into the multifaceted dynamics of environmental attitudes and behaviours, underscoring the importance of considering various factors in addressing environmental issues.